2016
DOI: 10.1123/mc.2014-0064
|View full text |Cite
|
Sign up to set email alerts
|

Movement Adjustments Have Short Latencies Because There is No Need to Detect Anything

Abstract: We can adjust an ongoing movement to a change in the target's position with a latency of about 100 ms, about half of the time that is needed to start a new movement in response to the same change in target position (reaction time). In this opinion paper, we discuss factors that could explain the difference in latency between initiating and adjusting a movement in response to target displacements. We consider the latency to be the sum of the durations of various stages in information processing. Many of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 69 publications
4
46
0
Order By: Relevance
“…For example, it was found that correction latency was significantly longer for movements to visual targets perturbed towards the body compared to visual targets perturbed away from the body. These findings are therefore consistent with the hypothesis that detection processes have very little influence on correction processes during ongoing reaching movements (Smeets et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…For example, it was found that correction latency was significantly longer for movements to visual targets perturbed towards the body compared to visual targets perturbed away from the body. These findings are therefore consistent with the hypothesis that detection processes have very little influence on correction processes during ongoing reaching movements (Smeets et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…et al Brenner 2013) or is not noticed by the participant (Goodale et al 1986;Prablanc and Martin 1992). That the displacement does not have to be detected for corrections to be made shows that the adjustments are manifestations of a mechanism that continuously updates the estimate of the target location and guides the movement to that location (Brenner and Smeets 2017;Smeets et al 2016). The latency of the adjustment depends on how much time it takes to process the relevant sensory information and thus on the properties of the target (Veerman et al 2008).…”
Section: How Movements Are Controlled Continuouslymentioning
confidence: 99%
“…R eaction times can be used to judge how long it takes to process various things about external signals (Donders, 1868(Donders, , 1969. Detecting the presence of a stimulus, recognizing it, selecting a suitable response, and planning and executing the response, all take time (Smeets, Oostwoud Wijdenes, & Brenner, 2016). It takes longer to initiate a motor response to a stimulus if the stimulus is less intense, if the stimulus has to be recognized rather than only detected, if there are several possible responses to choose from, and so on (Teichner & Krebs, 1972, Teichner & Krebs, 1974.…”
Section: Introductionmentioning
confidence: 99%